কাবুলের ক্যারাভান সরাই - সুলতান, মঈনুস (ঢাকা প্রথমা প্রকাশন, 2018)
Author's travelogue to Afghanistan.
Residential Campus
GenEd (Residential Campus)
Development Book Agency
In Bengali.
Keywords: Sulatāna, Maīnusa -- Travel -- Afghanistan; Afghanistan -- Description and travel